Spatiotemporal Variation in Agricultural Drought Conditions in Northwestern Bangladesh under a Changing Climate (Journal of the Bangladesh Agricultural University, 2026)
Drought threatens agriculture and water security in northwestern Bangladesh, yet its multi-scale seasonal characteristics remain insufficiently understood. This study assessed SPEI-based drought variability at six meteorological stations across 1-, 3-, 6-, 9-, 12-, and 24-month scales. Monthly precipitation and temperature records from 1976–2022 were used to calculate SPEI. Seasonal drought was evaluated for Rabi (November–February), Kharif-I (March–June), and Kharif-II (July–October) using the four-month SPEI ending in February, June, and October, respectively. Trends were examined using the Mann–Kendall test and Sen’s slope estimator, with magnitude expressed as SPEI units yr⁻¹. Drought conditions were classified using SPEI values as mild (-0.99 to 0.00), moderate (-1.49 to -1.00), severe (-1.99 to -1.50), and extreme drought (≤ -2.00). Drought frequency in each drought category was compared between earlier and recent periods. Drought calculated from SPEI values increased across most stations and time scales, with stronger intensification at longer scales. Among stations considered, Rajshahi showed the steepest long-term decline at SPEI-24 (Sen’s slope = -0.0538 SPEI units yr⁻¹), followed by Syedpur, Bogura, Rangpur, Ishwardi, and Dinajpur. Extreme drought at SPEI-24 became more frequent during 2006–2022, reaching 19.1% of valid months in Bogura, 23.0% in Rajshahi, and 20.6% in Rangpur. Kharif-II drought increased at Bogura and Dinajpur (-0.04 SPEI units yr⁻¹) and at Rajshahi and Rangpur (-0.03 SPEI units yr⁻¹), suggesting increasing water stress during the late-monsoon to post-monsoon transition. Rangpur and Dinajpur (-0.03 and -0.05 SPEI units yr⁻¹, respectively) also experienced significant drought stress during Rabi season, while Kharif-I drought trends were weak and mostly non-significant. Overall, drought conditions in northwestern Bangladesh are becoming more persistent and seasonally consequential, supporting multi-scale SPEI monitoring for irrigation scheduling, seasonal preparedness, and climate-resilient agricultural planning.J Bangladesh Agril Univ 24(2): 144–156, 2026